Reliability of hematoma volume measurement at local sites in a multicenter acute intracerebral hemorrhage clinical trial - Hussein, Haitham M (2012)
BACKGROUND AND PURPOSE: The reliability of hematoma volume (HV) measurement using the ‘ABC/2’ method in multicenter clinical trials is unknown. We determined the accuracy of ABC/2 method as an on-site test in comparison with the gold standard central HV-assessment and semiautomatic HV-assessment. METHOD: We analyzed data from an acute intracerebral hemorrhage (ICH) multicenter clinical trial. HV was measured by site investigators to determine enrollment eligibility (<60 cm(3)) using the ABC/2 method (on-site HV), and independently by the core-imaging laboratory using computer-based analysis (MIPAV HV). HV was also measured by ABC/2 method (central HV) at the core-imaging laboratory to assess the difference in measurements between on-site (multiple raters with variable experiences) and central (single experienced rater) HVs. RESULTS: Fifty-six subjects were analyzed (mean age 62±15 years; 45% women). On site HV values showed a significantly lower correlation with the MIPAV HV (r=0.63) than central HV and MIPAV HV (r=0.93) values. The correlation between on-site HV and central HV values was modest (r=0.51). A total of 73% of the central HVs were within 25% of the corresponding MIPAV HVs, whereas only 46% of the on-site HVs was within 25% of the corresponding MIPAV HVs (p<0.001). One protocol violation occurred due to inaccuracy of on-site HV measurement. CONCLUSION: On-site HV measurements showed high variability but the impact on the eligibility determination was small. Centralized re-measurements of HVs with feedback to the sites may increase the reliability of the on-site HV measurements.